The Influence of Work Motivation, Work Discipline and Work Environment on Job Satisfaction - Muhammad Fikri Hakim; Muhammad Anhar; Dian Surya Sampurna (BPJP - STEI, 2021)
This study aims to determine how the influence of work motivation, work discipline, and work environment on the job satisfaction of employees of BRI Sharia Bank KC Jakarta Wahid Hasyim. This research method is a quantitative method using primary data. The number of samples in this study was 98 employees. Data processing in this study used the SmartPLS analysis tool and used Partial Least Square (PLS) analysis. The analysis used in this study includes outer model analysis, coefficient determination, f square test, and internal model analysis. The results show that (1) work motivation has a positive and significant effect on job satisfaction, (2) work discipline has a negative but not significant effect on job satisfaction, and (3) work environment has a positive and significant effect on job satisfaction.